PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA AKADEMI PARIWISATA X - Setyo Widiarto; Sulih Wahyudiono (LPPM and Travel Operation Department Universitas Asa Indonesia, 2018)
This study aimed to determine the effects of compensation and motivation on employees’ performance in Akademi Pariwisata X. Compensation and motivation are dependent variables denoted as X1 and X2, while performance is independent variable denoted as Y. Data are collected through questionaire which are then analyzed using SPSS (Statistical Product and service Solution) version 20. Respondents of this study are 25 employees of Akademi Pariwisata X. The method used in this study is Multiple Linear Regression test. The results of this study show that independent variables (compensation and motivation) are simultaneously capable to explaining the diversity of the dependent variables (employees’ performance) of 28.009%, while the rest, 71.991% are affected by other variables which are not discussed in this research such as leadership, coordination, organization, tools, work condition and work climate.